Response of growth and tuber seed production of G0 potato (Solanum tuberosum L.) cv Medians in medium lands of Jatinangor to biochar composition and retardant type - Dewi, Tessa Prima; Hamdani, Jajang Sauman; Mubarok, Syariful (Kultivasi, 2024)
Potatoes are the third most consumed food in Indonesia. The availability of high-quality potato tuber seeds is still low which affects potato production. Potato planting in the highlands is limited, so it needs to be expanded into medium lands. The modification that can increase the production of G0 potato tuber seeds on medium lands is the use of biochar and retardant. The purpose of this research was to determine the composition of biochar and the type of retardant to increase the G0 tuber seed yield of potato cv Medians in the medium lands of Jatinangor. The research was conducted from August 2022 to February 2023 at the Station Ciparanje, Jatinangor, Faculty of Agriculture, Universitas Padjadjaran. The experiment used Factorial Randomized Block Design (RBD). The first factor was the biochar compositions: b1 (100% compost), b2 (80% compost + 20% rice husk biochar), b3 (80% compost + 20% coconut shell biochar), and b4 (80% compost + 10% biochar husk rice + 10% coconut shell biochar). The second factor was the retardant type: r1 (without retardant), r2 (100 ppm paclobutrazol), and r3 (100 ppm prohexadione-Ca). The experimental results showed that there was no interaction effect of biochar compositions and retardant type on the growth and yield of G0 potato tuber seeds. Treatment of 80% compost + 20% coconut shell biochar suppressed plant height but increased the number of tubers. Treatment of 100 ppm paclobutrazol resulted in lower plant height but total chlorophyll content, percentage of stolon forming tubers, the number of tubers, and tuber weight per plant were higher compared to treatments without retardant and with 100 ppm prohexadione-Ca.